Pembelajaran Bermakna Berbasis Teori Ausubel Menurut As-Sarqawi Dalam PAI - Jannah, Wirwahatul; Muhlis, Achmad (LPPAIK Universitas Muhammadiyah Bandung, 2025)
The teaching of Islamic Religious Education (PAI) in schools often emphasizes memorization, which tends to neglect the practical application of Islamic values in daily life. This article aims to examine the integration of Ausubel’s meaningful learning theory with As-Sarqawi’s perspective as an effort to create more effective PAI learning. The method used is a literature review through the analysis of relevant books, journals, and articles. The findings indicate that Ausubel’s concept of advance organizers can be applied through Qur’anic verses or Hadiths as the initial framework of learning. Integrating this with As-Sarqawi’s concept of ta’dib ensures that learning not only enriches knowledge but also shapes Islamic character. In topics such as gossip (gibah) and verification of information (tabayun), this model helps students understand the concepts deeply while fostering critical awareness in the digital era. Thus, the integration of Ausubel and As-Sarqawi presents PAI learning that is meaningful, contextual, and relevant to modern challenges.